Melissopalynological Analysis Revealed a Higher Pollen Diversity in Stingless Bees than in Honey Bees - Sayusti, Tiara; Raffiudin, Rika; Djuita, Nina Ratna; Perwitasari-Farajallah, Dyah; Batubara, Irmanida; Priawandiputra, Windra; Sitompul, Rahmadi; Jahnk, Svea Lina; Behling, Hermann (HAYATI Journal of Biosciences, 2026)
Identifying floral resources used by honey bees and stingless bees is essential for sustainable beekeeping and understanding pollination ecology. This study compared the diversity of floral resources utilized by the honey bee Apis cerana and stingless bees Geniotrigona thoracica and Heterotrigona itama based on pollen in honey. Bee colonies were in the same Flora Nauli Beekeeping area, Pematang Siantar, North Sumatra, Indonesia, ensuring equal access to similar surrounding floral resources. Honey samples were collected, and pollen grains were extracted, acetolysed, and analyzed by counting 1,200 grains to determine frequency classes. Pollen diversity was calculated using the Shannon–Wiener index (H′). Stingless bee honey contained more diverse pollen than A. cerana, which only contained pollen from the Arecaceae family. Heterotrigona itama and G. thoracica honey contained pollen from 20 and 11 plant families, respectively. Each species had a distinct predominant pollen type (>45%): Cocos nucifera (A. cerana), Sapotaceae type (G. thoracica), and Casuarinaceae type (H. itama). A higher pollen diversity index was also observed in H. itama (1.05-1.83) than in G. thoracica (0.34–1.64) and A. cerana (0.66). These results indicate that stingless bees are more generalist than honey bees, highlighting their ecological role in supporting pollination networks in tropical agroecosystems.